Study of antimicrobial and anticancer activity of new synthetic and natural tools - Dhanyalayam, Dhanya; Andò, Sebastiano; Cappello, Anna Rita (My University, 2017)
Infectious diseases and cancer are the two disease groups that representing the major cause of death worldwide. Unfortunately, antibiotic resistance is the biggest threat in the first case; in fact, new resistance mechanisms continuously are emerging and spreading globally, threatening the ability to treat common infectious diseases. A growing list of infections caused by bacteria, viruses, parasites etc. are becoming harder and harder to treat, and sometimes impossible, as antibiotics become less effective. Without urgent action, we are heading for a post-antibiotic era, in which common infections and minor injuries can once again kill the human population. Concerning cancer, Resistance to chemotherapy and molecularly targeted therapies is a major problem in current research. Drugs side effects and toxicity to normal body cells is also an important threat in cancer treatments. In this regard, these problems are at the forefront of scientific research and technological innovation and are leading to the development of new therapeutic approaches against cancer and infectious disease with fewer side effects and lesser resistance problems. The aim of the present study was to investigate on the new compounds in order to find new possible therapeutic agents against bacteria, parasites and cancer. Infectious diseases are caused by microorganisms such as bacteria, parasites, viruses etc.; in particular, bacterial infectious diseases are caused by either Gram +ve or Gram -ve bacteria. Certainly, antibiotics are the main weapon against infectious bacterial diseases; however, the uncontrolled use of antibiotics to control infections in humans, animals and in agriculture caused the development of drug resistance by bacterial populations. Besides this, infections caused by Gram -ve bacteria are difficult to treat due to the presence of a protective outer membrane consisting of lipopolysaccharides. Therefore, it is clear that there is a need to develop novel classes of antibacterial agents capable of killing bacteria through mechanisms unlike those of the known classes of antibiotics. Then, scientists are currently searching for new approaches to treat infectious diseases, particularly those caused by Gram -ve bacteria, focusing on exactly how the pathogens change and how drug resistance evolves. Since ancient times, metal complexes have been used as antibacterial compounds, metallic silver and silver salts are good examples of this. Silver compounds are particularly interesting since their antibacterial activity can be altered by changing the ligand associated with the silver complex. To date, among silver derivatives, silver sulfadiazine remains one of the most commonly-used antibacterial drugs. Therefore, metal N-heterocyclic carbene (MNHC) complexes appeared as an emerging field of research in medicinal chemistry where NHC complexes of coinage metals (Cu, Au, and Ag) proved to be better antimicrobial agents. Herein, it was investigated the, in vitro, antibacterial activity of the newly synthesized silver (Ag) complexes, Iodide[N-methyl-N-(2-hydoxy-cyclopentyl-imidazole-2ylidine]silver(I), Iodide[N-methyl-N-(2-hydoxy-cyclohexyl)-imidazole-2-ylidine]silver(I) and Iodide[N-methyl- N-(2-hydoxy-2-phenyl)ethyl-imidazole-2-ylidine]silver(I), namely AgL6, AgL18 and AgL20, against two Gram +ve (Staphylococcus aureus, Streptococcus pyogenes) and three Gram -ve (Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa) bacteria. Among these, AgL6 showed good antibacterial activity against both Gram +ve and Gram -ve bacteria. However, the minimum inhibitory concentration (MIC) value was 32 μg/mL for Gram +ve and 16 μg/mL for Gram -ve bacteria, which was higher than that displayed by commercial drug, used as control (Silver Sulfadiazine, AgSD). We therefore hypothesized that the poor activity is due to the poor intake of the compound. In order to enhance its antibacterial activity, we have developed “a pharmaceutically-oriented device”, a nanocarrier as a tool for targeted drug delivery. Here it was described, for the first time, the production of a polymer nanostructure in which dextran, a biopolymer, and oleate residues represent the hydrophilic and hydrophobic parts, respectively. This nanoparticle was loaded with AgL6 and the antibacterial activity has been investigated. The results were very interesting, with MIC values being reduced four-fold for both Gram +ve and Gram -ve bacteria. Surprisingly, these values were two-fold lower than for silver sulfadiazine. Briefly, our results showed that K. pneumoniae and E. coli are the most susceptible bacteria to AgL6, followed by P. aeruginosa. In conclusion, the investigated compound AgL6 showed excellent potentiality against bacterial infections. According to the World Health Organization (WHO), 17 diseases caused by bacteria and parasites have been classified as neglected tropical diseases (NTDs). NTDs are endemic in 149 tropical and subtropical countries and affect more than 1 billion people, including 875 million children. These diseases are responsible for over 500,000 deaths per year and are characterized by severe pain and long term disability. Human African Trypanosomiasis (sleeping sickness) is an important disease among them and is caused by two parasites of the genus Trypanosome: Trypanosome brucei rhodesiense and Trypanosome brucei gambiense. Trypanosomiasis is a disease with a devastating socio-economic impact in sub-Saharan Africa through direct infection of humans and livestock. This disease is fatal if left untreated. Current therapy relies on five drugs that have many limitations among which acute toxicity, problems with oral absorption and emergence of trypanosomal resistance, this latter is a major concern owing to the absence of vaccines and therapeutic alternatives. Therefore pharmaceutical research is aimed at the discovery of new drugs, although the investment in this therapeutic area is not attractive owing to the prospect of poor financial returns. Many pharmaceutical industries have already utilized an opportunistic approach by utilizing drugs long since used for other diseases, a process known as “repurposing” of the drug. It is estimated that over half of the drugs used today are derived from natural sources. In the present study, in a search for molecules with trypanocida activity, it was screened 2000 natural extracts from Fungi and Actinomycetes. The extracts showing activity were selected, and the active compound was identified by liquid chromatography and mass spectroscopy. Chaetocin is one of the molecules identified which showed good trypanocidal activity when tested in vitro. Chaetocin is already used as an antibacterial and anticancer drug, here it was repurposed as drug against trypanosomiasis. The results were very surprising because the trypanocidal activity was in the nanomolar range; the IC50 value was found to be 8.3 nM. Next, it was investigated on its mechanism of action. In chaetocin treated cells, morphological changes and chromatin degradation were identified, by fluorescence microscopy and cell-cycle arrest during the G2 phase was proven by cytometry analysis. Finally, it was hypothesized that the enzyme histone methyl transferase, an important enzyme acting in the G2 phase, could be the target for this drug.This study displayed that chaetocin could have great potentiality in the fight against the deadly trypanosomiasis. However, further studies will be needed to reveal whether this compound can cross the blood-brain barrier. In the third part of this thesis it was evaluated the synthesis and anticancer activity of some phosphonium salts. Phosphonium salts are a class of lipophilic cationic molecules that accumulate preferentially in mitochondria and inhibit the growth of human cancer cell lines The aim of the present study was to investigate the effects of a lipophilic phosphonium salt, (11-methoxy, 11-oxoundecyl)triphenylphosphonium bromide (MUTP) along with two other newly synthesized phosphine oxide salts, 3,3’-(methylphosphoryl)dibenzenaminium chloride and 3,3’-(phenylphosphoryl)dibenzenaminium chloride (SBAMPO and SBAPPO) on proliferation, in two human cancer cell lines: human breast cancer cells (MCF-7) and human uterine cervix adenocarcinoma cells (HeLa) and to elucidate their mechanism. The cancer cell mitochondrial membrane potential is relatively high when compared to normal cells, this force the phosphonium salts to accumulate, preferencially, in the mitochondria and inhibit their function. The results showed that only MUTP exhibits anti-proliferative effects on both cell lines, without affecting normal breast epithelial cell proliferation. More specifically, it was demonstrated that MUTP treatment of breast cancer cells is associated with impaired cell cycle progression, as determined by cytometry analysis. The G1/S cell cycle arrest was confirmed by an increased expression level of two proteins involved in cell cycle regulation, p21 and p53. Recently, there has been a surge of interest in developing compounds selectively targeting mitochondria for the treatment of neoplasms. The critical role of mitochondria in cellular metabolism and respiration supports this therapeutic rationale. Dysfunction in the processes of energy production and metabolism contributes to attenuation of response to pro-apoptotic stimuli and increased ROS production both of which are implicated in the initiation and progression of most human cancers. Therefore, in order to characterize the mitochondrial function in MCF7 cells, after MUTP treatment, the cells were stained with specific metabolic probes and analyzed by FACS. The outcomes displayed that MUTP treatment decreased mitochondrial mass and mitochondrial membrane potential and increased the ROS production. In agreement with these findings, the reduction in the expression of the mitochondrial oxidative pathway (OXPHOS) enzymes revealed a bioenergetics failure, induced by MUTP, in treated cells. TUNEL assay, DNA Laddering and Western blot analysis of caspase-3, caspase-9 and Bax confirmed the apoptotic effect of MUTP treatment. Taken together, all these data suggest that MUTP may be capable of selectively targeting neoplastic cell growth and therefore has potential applications as an anticancer agent.
Dottorato di Ricerca in Medicina Traslazionale. Ciclo XXIX
Keywords: Antimicrobial drug; Mitochondria